2020
DOI: 10.1111/jnc.15136
|View full text |Cite
|
Sign up to set email alerts
|

Substrate reduction therapy using Genz‐667161 reduces levels of pathogenic components in a mouse model of neuronopathic forms of Gaucher disease

Abstract: Most lysosomal storage diseases (LSDs) have a significant neurological component, including types 2 and 3 Gaucher disease (neuronal forms of Gaucher disease; nGD). No therapies are currently available for nGD since the recombinant enzymes used in the systemic form of Gaucher disease do not cross the blood–brain barrier (BBB). However, a number of promising approaches are currently being tested, including substrate reduction therapy (SRT), in which partial inhibition of the synthesis of the glycosphingolipids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…APOD and APOE, are involved in the removal of lipids during nerve cell degeneration [62], which may be of importance in demyelination. Moreover, levels of two PLIN proteins (PLIN 3 and 4) were elevated in the MLIV brain and in neuronal forms of Gaucher disease [63,64]. Lipid droplets have been implicated in neurodegeneration [65,66] including in Parkinson's disease, which suggest that they play a broad role in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…APOD and APOE, are involved in the removal of lipids during nerve cell degeneration [62], which may be of importance in demyelination. Moreover, levels of two PLIN proteins (PLIN 3 and 4) were elevated in the MLIV brain and in neuronal forms of Gaucher disease [63,64]. Lipid droplets have been implicated in neurodegeneration [65,66] including in Parkinson's disease, which suggest that they play a broad role in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A Phase III clinical trial of venglustat showed promise in improving biochemical and phenotypic parameters in GD3 patients [ 21 ]. An analogue of venglustat, GZ-682452 (termed herein as GZ452), was effective at attenuating several neuropathologic and behavioral manifestations associated with nGD mouse models [ 22 , 23 , 24 ]. However, the underlying mechanism(s) of SRT in protecting cellular functions are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…2 A). Tg2576 mice were fed either a control diet or a GCSi formulated diet, which we previously reported lowers glycosphingolipid levels and reduces neuropathological features of disease in mouse models of Gaucher disease [ 5 ], Parkinson disease [ 44 ], and amyotrophic lateral sclerosis [ 16 ]. In WT mice, regional variations in total GlcCer and GM3 levels were observed in the cortex, hippocampus, and amygdala (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Animals were housed under light: dark (12:12 h) cycles and provided with food and water ad libitum. In all GCSi treatment studies, compound (GENZ-667161) was administered at 60 mg/kg/day in formulated diet as previously described [ 5 , 16 , 31 , 44 ]. All procedures were performed using protocols approved by Sanofi Genzyme’s Institutional Animal Care and Use Committees.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation